On the link between soil hydromorphy and geomorphological development in the Cerrado (Brazil) wetlands - Rosolen, Vania [UNESP] (2019)
Mound fields (MF), which consist of numerous isolated mounds, are characteristic of the Cerrado wetlands of Brazil. While there are numerous studies on soil redistribution by termites and by differential particulate erosion, a new hypothesis, supported by metal accumulation in these areas, needs to be tested. This study aimed to investigate the extent to which soil saturation by water, and the associated chemical erosion, might be a key driver of the geomorphological development of the Cerrado wetlands. The study was performed in a typical wetland of Minas Gerais that shows a typical succession from well drained Ferralsols on the plateau to Gleysols on the lowland and the presence of MF at the transition. Soil morphological description was used together with optical microscopy, X-ray fluorescence and physical analyses (grain size and bulk density) to discriminate between the biological (bioturbation) and geochemical origins. Additionally, geochemical mass balance was calculated to estimate the total amount of chemical erosion that had occurred in the area. The morphological observations and the results on soil texture did not point to material redistribution in the MF. In contrast, the results showed that iron-depleted aggregates in depressed zones were sensitive to collapse. Soil saturation by water as the main cause of geochemical erosion and geomorphologic development was confirmed by mass balance calculation. The results fill an important information gap on the formation and evolution of cerrado soil landscapes, which have important consequences for biodiversity and water conservation.